MODEL EDUKASI DAN PERLINDUNGAN KONSUMEN BERBASIS MAQASHID SYARIAH PADA JAMINAN SOSIAL - Ridan Muhtadi; Anindya Yusuf Wirmanda; Gancar Candra Premananto (Ulumuna: Jurnal Studi Keilsman, 2019)
Human welfare from an Islamic perspective pays attention to a balanced satisfaction between material needs and spiritual needs. Some policies have been implemented by the government to improve social security to humanity, but the lack of spiritual morale and lack of coordination between the related institutions resulted in policies that have not been implemented optimally. Consumer protection, which is one part of optimizing programs, has not yet run coordinatively. Therefore, the writer has an idea that can be implemented, which is Maqashid Sharia-based Consumer Education and Protection on Social Security for Muslims, the Poor, the Poor, and Non-Muslims to achieve falah with aspects that are the dharuriyat needs namely maintenance of faith (din), soul (nafs), reason (aql), descent (nasl), wealth (maal). The implementation of education and consumer protection based on maqashid sharia is a government apparatus, BAZ, LAZ, UPZ, and awareness for fellow human beings to bear the needy and poor alike in order to achieve the benefit of the people. The research method used is a qualitative descriptive approach. The concept of education and consumer protection based on maqashid sharia can be a creative and productive solution related to various moral and spiritual problems and the management of social security, justice for the poor in getting social security as mandated in the 1945 Constitution and the Koran. In addition, the implementation of this program is expected to achieve the independence of the people and the achievement of falah for all people.